Gender Analysis of Crop and Animal Husbandry Practices in Hill Agriculture - Ashish Singh , N. V. Kumbhare , Premlata Singh , Nishi Sharma , Neelam Patel and Bishal Gurung (Indian Journal of Extension Education, 2016)
Women farmers have been the vital workforce in agriculture, as they manage agricultural activities along with thehousehold chores. The study was conducted in purposively selected Almora and Nainital districts of Uttarakhand, India.The two blocks each from Almora (Takula and Hawalbagh) and Nainital (Betalghat and Dhari) were selected randomly.Further, two villages from each block were selected randomly. Fifteen women and five men farmers from each villagewere selected through simple random sampling. Thus, a total of 120 women and 40 men respondents from two districtsconstituted the sample for the study. The study revealed gender gap in crop husbandry, animal husbandry and daily routinepractices in hill agriculture. The gender analysis in crop husbandry practices revealed that a majority of the womenfarmers were engaged in weeding (94.60%) followed by thinning and gap filling (87.82%), storage (82.23%), threshingand winnowing (74.77%), irrigation (70.52%), loading and unloading (63.58%) were the major activities done by womenfarmers. Agricultural activities like sowing (66.46 %), seed treatment (51.42%) and harvesting (52.33%) were done bywomen farmers with a significant help from men farmers. The activities like fodder cutting (88.27%) and cleaning animalshed (86.75%) were the activities demand larger time share of women farmers. Other activities like feed and fodder to theanimals (70.47%), milking (75.67%) and animal care (77.50%) were also majorly done by women. Most of the activitieslike food preparation (99.00%) followed by collection of fuel and fodder (97.00%), collecting water (89.40%) and familycare (88.20%) were the major time consuming activities done by the women farmers as compared to their malecounterpart.